Commissioning results of an automated treatment planning verification system. (8th September 2014) - Nelson, Christopher L.; Mason, Bryan E.; Robinson, Ronald C.; Kisling, Kelly D.; Kirsner, Steven M.
Abstract : A dose calculation verification system (VS) was acquired and commissioned as a second check on the treatment planning system (TPS). This system reads DICOM CT datasets, RT plans, RT structures, and RT dose from the TPS and automatically, using its own collapsed cone superposition/convolution algorithm, computes dose on the same CT dataset. The system was commissioned by extracting basic beam parameters for simple field geometries and dose verification for complex treatments. Percent depth doses (PDD) and profiles were extracted for field sizes using jaw settings 3   ×   3   cm 2   ‐   40   ×   40   cm 2 and compared to measured data, as well as our TPS model. Smaller fields of 1   ×   1   cm 2 and 2   ×   2   cm 2 generated using the multileaf collimator (MLC) were analyzed in the same fashion as the open fields. In addition, 40 patient plans consisting of both IMRT and VMAT were computed and the following comparisons were made: 1) TPS to the VS, 2) VS to measured data, and 3) TPS to measured data where measured data is both ion chamber (IC) and film measurements. Our results indicated for all field sizes using jaw settings PDD errors for the VS on average were less than 0.87%, 1.38%, and 1.07% for 6x, 15x, and 18x, respectively, relative to measured data. PDD errors for MLC field sizes were less than 2.28%, 1.02%, and 2.23% for 6x, 15x, and 18x, respectively. The infield profile analysis yielded results less than 0.58% for 6x, 0.61% for 15x, and 0.77% for 18x for the VS relative to measured data. Analysis of the penumbra region yields results ranging from 66.5% points, meeting the DTA criteria to 100% of the points for smaller field sizes for all energies. Analysis of profile data for field sizes generated using the MLC saw agreement with infield DTA analysis ranging from 68.8%–100% points passing the 1.5%/1.5 mm criteria. Results from the dose verification for IMRT and VMAT beams indicated that, on average, the ratio of TPS to IC and VS to IC measurements was 100.5   ±   1.9 % and 100.4   ±   1.3 %, respectively, while our TPS to VS was 100.1   ±   1.0 % . When comparing the TPS and VS to film measurements, the average percentage pixels passing a 3%/3 mm criteria based gamma analysis were 96.6   ±   4.2 % and 97   ±   5.6 %, respectively. When the VS was compared to the TPS, on average 98.1   ±   5.3 % of pixels passed the gamma analysis. Based upon these preliminary results, the VS system should be able to calculate dose adequately as a verification tool of our TPS. PACS number: 87.55.km